The effectiveness of fatigue on repositioning sense of lower extremities: systematic review and meta-analysis - Sayyadi, P.; Minoonejad, H.; Seidi, F.; Shikhhoseini, R.; Arghadeh, R. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Introduction An injury can significantly harm both individual and team performance. One of the most important risk factors for sports-related injuries, especially non-collision injuries, is fatigue. It seems that poor proprioception may play an essential role to impose athletes to further injuries. This systematic review and meta-analysis aimed to examine the effectiveness of fatigue on the repositioning sense of the lower extremity joints.